Learning and consolidation of verbal declarative memory in patients with posttraumatic stress disorder - Diener, Slawomira; Flor, Herta; Wessa, Michèle (Zeitschrift für Psychologie, 2010)
Impairments in declarative memory have been reported in posttraumatic stress disorder (PTSD). Fragmentation of explicit trauma-related memory has been assumed to impede the formation of a coherent memorization of the traumatic event and the integration into autobiographic memory. Together with a strong non-declarative memory that connects trauma reminders with a fear response the impairment in declarative memory is thought to be involved in the maintenance of PTSD symptoms. Fourteen PTSD patients, 14 traumatized subjects without PTSD, and 13 non-traumatized healthy controls (HC) were tested with the California Verbal Learning Test (CVLT) to assess verbal declarative memory. PTSD symptoms were assessed with the Clinician Administered PTSD Scale and depression with the Center of Epidemiological Studies Depression Scale. Several indices of the CVLT pointed to an impairment in declarative memory performance in PTSD, but not in traumatized persons without PTSD or HC. No group differences were observed if recall of memory after a time delay was set in relation to initial learning performance. In the PTSD group verbal memory performance correlated significantly with hyperarousal symptoms, after concentration difficulties were accounted for. The present study confirmed previous reports of declarative verbal memory deficits in PTSD. Extending previous results, we propose that learning rather than memory consolidation is impaired in PTSD patients. Furthermore, arousal symptoms may interfere with successful memory formation in PTSD.
Online veröffentlicht: February 26, 2015
Gesehen am 08.05.2023